Fault-tolerant flight control and guidance systems practical methods for small unmanned aerial vehicles - Ducard, Guillaume J.J (Advances in industrial control, 2009)
This book offers a complete overview of fault-tolerant flight control techniques. Discussion covers the necessary equations for the modeling of small UAVs, a complete system based on extended Kalman filters, and a nonlinear flight control and guidance system.